Tinjauan Yuridis Terhadap Pembinaan Narapidana dalam Upaya Pencegahan Tindakan Residivis (Studi Kasus di Rutan Kelas I Surakarta) - Supriyono; Putra, Yuka Asmara (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The purpose of this study is to find out what factors affect inmates to recidivist, and to find out how the form of inmate coaching so that recidivism does not occur in the Class I State Prison in Surakarta. This research was carried out in Bantaeng district, precisely in the Class I State Prison of Surakarta. The approach method used in the preparation of this thesis is an empirical juridical approach. Data collection techniques are carried out by interviews, observations, questionnaires, and documentation. Furthermore, the data obtained from the results of research in the field were analyzed using quantitative analysis studies. Based on the results of the study, the author draws the conclusion that the factors that affect inmates to repeat criminal acts are: economic problems, social environment, lack of supervision from parents, the role of information and technology developments that have a negative impact, lack of education and form of coaching carried out by Surakarta Class I State Prison officers in preventing the repetition of criminal acts just like the coaching of inmates in general, including spiritual mental coaching. Officers of the Surakarta Class I State Prison also provide training programs and skills development such as making handicrafts by utilizing used materials such as making ashtrays, cabinets, mirrors, photo frames from newspapers, sewing coaching, fish farming coaching, motorcycle repair coaching, coaching the making of iron fences for inmates as a provision for working capital after serving their sentences. The implication of this study is that it is hoped that the guidance provided to inmates is more optimal, so it is necessary to cooperate with the community and is expected to provide special guidance to recidivist prisoners. In order for the coaching to run well, the human resources of correctional officers need to be increased and improved so that they have sufficient provisions in carrying out their duties. Keywords: recidivist, inmate, prison Abstrak Tujuan yang hendak dicapai dalam penelitian ini adalah ntuk mengetahui faktor-faktor apa yang memengaruhi narapidana melakukan residivis, dan Untuk mengetahui bagaimana bentuk pembinaan narapidana agar tidak terjadi Residivis di Rumah Tahanan Negara Kelas I Surakarta. Penelitian ini dilaksanakan di kabupaten Bantaeng, tepatnya di Rumah Tahanan Negara Kelas I Surakarta. Metode pendekatan yang digunakan dalam penyusunan skripsi ini adalah pendekatan yuridis empiris. Teknik pengumpulan data dilakukan dengan wawancara, observasi, kuisioner, dan dokumentasi. Selanjutnya data yang diperoleh dari hasil penelitian dilapangan dianalisis dengan menggunakan studi analisis kuantitatif. Berdasarkan hasil penelitian, penulis menarik kesimpulan bahwa faktorfaktor yang memengaruhi narapidana melakukan pengulangan tindak pidana yaitu: masalah ekonomi, lingkungan pergaulan, kurangnya pengawasan dari orang tua, peran dari perkembangan informasi dan teknologi yang berdampak negatif, kurangnya pendidikan dan bentuk pembinaan yang dilakukan petugas Rumah Tahanan Negara Kelas I Surakarta dalam mencegah terjadinya pengulangan tindak pidana sama seperti pembinaan narapidana pada umumnya diantaranya, pembinaan mental kerohanian. Petugas Rumah Tahanan Negara Kelas I Surakarta juga memberikan program pelatihan dan pembinaan keterampilan seperti pembuatan kerajinan tangan dengan memanfaatkan bahan bekas seperti pembuatan asbak, lemari, cermin, bingkai foto dari Koran, pembinaan menjahit, pembinaan budi daya ikan, pembinaan memperbaiki kendaraan motor, pembinaan pembuatan pagar besi bagi narapidana sebagai bekal modal kerja selepas menjalani masa pidananya. Implikasi dari penelitian ini adalah diharapkan pembinaan yang diberikan kepada narapidana lebih optimal, maka perlu dilakukan kerjasama dengan masyarakat dan diharapkan melakukan pembinaan khusus kepada narapidana residivis. Agar pembinaan berjalan dengan baik, maka sumber daya manusia petugas pemasyarakatan perlu tambah dan ditingkatkan sehingga memiliki bekal yang cukup dalam melakukan tugasnya. Kata Kunci : Residivis, Narapidana, Rutan